The durability of endovascular coiling versus neurosurgical clipping of ruptured cerebral aneurysms: 18 year follow-up of the UK cohort of the International Subarachnoid Aneurysm Trial (ISAT) - Molyneux, Andrew J (Lancet, 2015)
BACKGROUND: Previous analyses of the International Subarachnoid Aneurysm Trial (ISAT) cohort have reported on the risks of recurrent subarachnoid haemorrhage and death or dependency for a minimum of 5 years and up to a maximum of 14 years after treatment of a ruptured intracranial aneurysm with either neurosurgical clipping or endovascular coiling. At 1 year there was a 7% absolute and a 24% relative risk reduction of death and dependency in the coiling group compared with the clipping group, but the medium-term results showed the increased need for re-treatment of the target aneurysm in the patients given coiling. We report the long-term follow-up of patients in this UK cohort. METHODS: In ISAT, patients were randomly allocated to either neurosurgical clipping or endovascular coiling after a subarachnoid haemorrhage, assuming treatment equipoise, between Sept 12, 1994, and May 1, 2002. We followed up 1644 patients in 22 UK neurosurgical centres for death and clinical outcomes for 10·0–18·5 years. We assessed dependency as self-reported modified Rankin scale score obtained through yearly questionnaires. Data for recurrent aneurysms and rebleeding events were collected from questionnaires and from hospital and general practitioner records. The Office for National Statistics supplied data on deaths. This study is registered, number ISRCTN49866681. FINDINGS: At 10 years, 674 (83%) of 809 patients allocated endovascular coiling and 657 (79%) of 835 patients allocated neurosurgical clipping were alive (odds ratio [OR] 1·35, 95% CI 1·06–1·73). Of 1003 individuals who returned a questionnaire at 10 years, 435 (82%) patients treated with endovascular coiling and 370 (78%) patients treated with neurosurgical clipping were independent (modified Rankin scale score 0–2; OR 1·25; 95% CI 0·92–1·71). Patients in the endovascular treatment group were more likely to be alive and independent at 10 years than were patients in the neurosurgery group (OR 1·34, 95% CI 1·07–1·67). 33 patients had a recurrent subarachnoid haemorrhage more than 1 year after their initial haemorrhage (17 from the target aneurysm). INTERPRETATION: Although rates of increased dependency alone did not differ between groups, the probability of death or dependency was significantly greater in the neurosurgical group than in the endovascular group. Rebleeding was more likely after endovascular coiling than after neurosurgical clipping, but the risk was small and the probability of disability-free survival was significantly greater in the endovascular group than in the neurosurgical group at 10 years. FUNDING: UK Medical Research Council.